2021
DOI: 10.1159/000512316
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Supervised Training Therapy on Pulmonary Arterial Compliance and Stroke Volume in Severe Pulmonary Arterial Hypertension and Inoperable or Persistent Chronic Thromboembolic Pulmonary Hypertension

Abstract: <b><i>Background:</i></b> Pulmonary arterial compliance (PAC) is a prognostic parameter in pulmonary arterial hypertension (PAH) reflecting the elasticity of the pulmonary vessels. <b><i>Objectives:</i></b> The objective of this post hoc analysis of a prospective randomized controlled trial (RCT) was to assess the effect of exercise training on PAC and stroke volume (SV) in patients with PAH and persistent/inoperable chronic thromboembolic pulmonary hypertension … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Pulmonary hypertension is a clinical condition in which there is an increase in pulmonary circulation pressure, characterized by an average pulmonary artery pressure >25 mmHg at rest, an expiratory pulmonary artery wedge pressure of 15 mmHg, and pulmonary vascular resistance > 3 wood units. (5) Pulmonary hypertension can usually be divided into idiopathic pulmonary arterial hypertension and those associated with congenital heart disease, systemic-to-pulmonary shunts, rheumatic diseases, portal hypertension, and human immunodeficiency virus infection. (6) In pulmonary hypertension, the pulmonary vascular lesions primarily involve the small pulmonary arteries (<500 mm in diameter).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pulmonary hypertension is a clinical condition in which there is an increase in pulmonary circulation pressure, characterized by an average pulmonary artery pressure >25 mmHg at rest, an expiratory pulmonary artery wedge pressure of 15 mmHg, and pulmonary vascular resistance > 3 wood units. (5) Pulmonary hypertension can usually be divided into idiopathic pulmonary arterial hypertension and those associated with congenital heart disease, systemic-to-pulmonary shunts, rheumatic diseases, portal hypertension, and human immunodeficiency virus infection. (6) In pulmonary hypertension, the pulmonary vascular lesions primarily involve the small pulmonary arteries (<500 mm in diameter).…”
Section: Discussionmentioning
confidence: 99%
“…(4) Thus, exercise training can be an alternative therapy to improves peak oxygen consumption and haemodynamics in patients with PH. (5) In this case report, we discuss Pulmonary Hypertension in ASD who are given therapy in the form of exercise training, and the results show that exercise training can improve the quality of life in patients in addition to providing pharmacological therapy.…”
Section: Introductionmentioning
confidence: 98%
“…In addition, a post-hoc analysis of right heart catheterization data showed a significant improvement of PAC by exercise training in PAH and CTEPH [57]. Low-dose exercise training at 4-7 days/week significantly improved PAC (training group 0.33 ± 0.65 mL/mmHg vs. control group −0.06 ± 1.10 mL/mmHg; mean difference 0.39 mL/mmHg, 95% confidence interval (CI) 0.15 to 0.94 mL/mmHg; p = 0.004) and stroke volume (training group 9.9 ± 13.4 mL/min vs. control group −4.2 ± 11.0 mL/min; mean difference 14.2 mL, 95% CI 6.5 to 21.8 mL; p < 0.001) in the training vs. control group [57]. These findings suggest that supervised exercise training might improve RV function and PAC at the same time.…”
Section: Treatment Effects On Right Heart Size and Functionmentioning
confidence: 96%
“…In patients with PAH, the SV correlates with World Health Organization functional class and its change during exercise was a predictor of morbidity and mortality (28)(29)(30). Additionally, a post hoc analysis of randomized control trials in patients with PAH and chronic thromboembolic pulmonary hypertension (CTEPH) showed that exercise training increased SV at 15 weeks by an average of 14.2 mL (31).…”
Section: Stroke Volume (Sv)mentioning
confidence: 99%